2011
DOI: 10.3855/jidc.2189
|View full text |Cite
|
Sign up to set email alerts
|

Rocky Mountain spotted fever in Panama: a cluster description.

Abstract: Rocky Mountain spotted fever (RMSF) is a tick-borne infection caused by Rickettsia rickettsii. We report a cluster of fatal cases of RMSF in 2007 in Panama, involving a pregnant woman and two children from the same family.  The woman presented with a fever followed by respiratory distress, maculopapular rash, and an eschar at the site from which a tick had been removed.  She died four days after disease onset.  This is the second published report of an eschar in a patient confirmed by PCR to be infected with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 22 publications
0
25
0
6
Order By: Relevance
“…10 In R. rickettsii infection, the presence of an inoculation eschar is an unusual finding (only five cases reported in the literature from 1981 to 2012). [11][12][13][14] The geographical distribution of R. rickettsii, the most pathogenic species of the tick-borne rickettsiae, is limited to the Western Hemisphere where its primary vectors are ticks of the genera Dermacentor, Rhipicephalus, and Amblyomma (Table 1). 15 …”
Section: With Centripetal Rash Distributionmentioning
confidence: 99%
“…10 In R. rickettsii infection, the presence of an inoculation eschar is an unusual finding (only five cases reported in the literature from 1981 to 2012). [11][12][13][14] The geographical distribution of R. rickettsii, the most pathogenic species of the tick-borne rickettsiae, is limited to the Western Hemisphere where its primary vectors are ticks of the genera Dermacentor, Rhipicephalus, and Amblyomma (Table 1). 15 …”
Section: With Centripetal Rash Distributionmentioning
confidence: 99%
“…Unfortunately, although BSF is a reportable disease, a lack of prompt initiation of the anti-rickettsial treatment has been frequently observed in Brazil, where BSF has wrongly been approached as a diagnosis of exclusion. Family clusters are a well-recognized feature of rickettsial disease caused by R. rickettsii and other SFGR, but few cases associated with occupational exposure have been described [7,[12][13][14]. However, studies demonstrate that workers occupationally exposed to tick bites are under significantly increased risk of other SFGR infections [4].…”
Section: Casementioning
confidence: 99%
“…1). Interestingly, while low-, mild-, and high-virulent strains of R. rickettsii have been reported in the eastern and western parts of the United States (20,22), only highvirulent strains, responsible for high fatality rates, have been reported in Central/South America, regardless of the tick vector (2,(23)(24)(25)(26)(27)(28)(29). While our results of no polymorphisms among Central/ South American isolates was biased because most of these isolates were derived from fatal cases, a recent study reported the same clade distribution as shown in our Fig.…”
mentioning
confidence: 99%